STUDY ON EXTRACTION AND PURIFICATION OF TRANS-RESVERATROL FROM VINE WASTE - A REVIEW - Alina Lenuța CRĂCIUN (Food and Environment Safety, 2021)
Resveratrol (3, 4', 5-trihydroxystilbene) is a natural phenolic compound synthesized by plants in response to various stressful circumstances (mechanical injury, siege of bacteria or fungi and UV exposure). Commercial resveratrol supplements on the market are mostly extracted from Japanese knotweed. As it grows even in heavily polluted environments and the presence of emodin, which is a compound that may have laxative effects and is found in partially purified extracts, additional concerns about the safety of these commercial preparations were raised. An alternative source of resveratrol intensely studied in recent years is vine waste, with recent studies showing high concentrations of resveratrol in extracts. In the last years, the researcher’s attention is focused on obtaining an efficient method of extraction and purification of this compound from the vine waste to show that this material can be used as a raw material for production of commercial supplements of resveratrol.